GaN-Based High-k Praseodymium Oxide Gate MISFETs with P2S5/(NH4)2SX + UV Interface Treatment Technology - Chao-Wei Lin; Hsien-Chin Chiu (Active and Passive Electronic Components)
This study examines the praseodymium-oxide- (Pr2O3-) passivated AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors (MIS-HEMTs) with high dielectric constant in which the AlGaN Schottky layers are treated with P2S5/(NH4)2SX + ultraviolet (UV) illumination. An electron-beam evaporated Pr2O3 insulator is used instead of traditional plasma-assisted chemical vapor deposition (PECVD), in order to prevent plasma-induced damage to the AlGaN. In this work, the HEMTs are pretreated with P2S5/(NH4)2SX solution and UV illumination before the gate insulator (Pr2O3) is deposited. Since stable sulfur that is bound to the Ga species can be obtained easily and surface oxygen atoms are reduced by the P2S5/(NH4)2SX pretreatment, the lowest leakage current is observed in MIS-HEMT. Additionally, a low flicker noise and a low surface roughness (0.38 nm) are also obtained using this novel process, which demonstrates its ability to reduce the surface states. Low gate leakage current Pr2O3 and high-k AlGaN/GaN MIS-HEMTs, with P2S5/(NH4)2SX + UV illumination treatment, are suited to low-noise applications, because of the electron-beam-evaporated insulator and the new chemical pretreatment.